Estudo da bula de medicamentos: Uma análise da situação - Da Silva, Marcia [UNESP]; Almeida, Adelia Emilia de [UNESP]; Oliveira, A. M. [UNESP]; Correia, C. C. [UNESP]; Benzatti, F. P. [UNESP]; Fernandes, J. T. [UNESP]; Barbosa, G. R. [UNESP]; Pimenta, C. P. [UNESP]; Costa, T. M M [UNESP]; Doneida, V. C. [UNESP] (My University, 2006)
This study was carried out in the city of Araraquara (SP, Brazil), where 1829 people selected randomly from 42 districts were interviewed with regard to their use of medicines, in particular whether and how they read the insert information sheet and the most frequently read items and problems encountered in the text. Surveys were performed in two stages, the first when package inserts were regulated in Brazil by Portaria SVS 110/1997 (Ministry of Health directive) and the second after the new regulation (RDC 140/2003) came into force. Out of 1829 people interviewed, 1597 reported using some medicine. The markedly similar results in both stages of the research pointed to the difficulties encounteved in reading the package inserts, due to the small letters, the obscure language and the massive amount of information. This paper shows that package inserts of medicines need to be simpler, so the patients have an idea of the importance of the medicine and are able to realize soon any problem that might appear due to the use of the medicine and what action they should take. Furthermore, it will be helpful to the evaluation of the package inserts of medicines, elaborated in conformity with RDC 140, if they work effectively as a source of information and guidance for the patient are not simply given a new layout, while maintaining items that impede their understanding and use.

Estudo desenvolvido na cidade de Araraquara-SP-Brasil, onde foram entrevistadas 1829 pessoas, moradores de 42 bairros, selecionadas aleatoriamente. Foram feitas perguntas acerca da utilização de medicamentos tais como, os itens mais lidos na bula, dificuldades encontradas na leitura da bula, etc. A entrevista foi realizada em duas etapas, a primeira quando em vigor a Portaria 110/97, a segunda, após a vigência da RDC 140/ 03, sendo que dos 1829 entrevistados, 1597 relataram estar fazendo uso de algum medicamento. Em ambas as etapas do trabalho, os resultados referentes às bulas foram semelhantes quanto ao tamanho reduzido da letra, a linguagem muito científica e a excessiva quantidade de informações utilizadas constituíram os fatores que dificultam sua leitura. Este trabalho, mostra que é necessário disponibilizar informações mais simples que permitam ao paciente vislumbrar a importância do conhecimento destas informações, estando apto a detectar problemas advindos do uso e sua imediata solução. Adiciona-se a isto a contribuição que traz para avaliação, se as bulas elaboradas conforme a RDC140/03 passarão a servir como fonte de informação e orientação do paciente, promovendo o uso racional do medicamento ou, se as bulas passarão apenas a apresentar uma nova formatação, mas com manutenção de fatores que prejudicam o seu entendimento e utilização.
An enquiry into pharmaceutical package inserts: Analysis of the current situation
Keywords: Medicines; Package inserts of medicines; Rational drugs use; analytic method; Brazil; controlled study; drug industry; drug information; drug packaging; human; interview; major clinical study; medicine; randomization